A conservação da fauna silvestre no interior paulista: concepções e criação de espaço educador em escola rural de Capivari – SP - Angelim, Karen Bertoldo (2017)
The conservation of biodiversity is crucial, but it is still an ambitious challenge in the development of Government Policies in the context of cities management. There has never been a study of the wildlife in rural areas in the city of Capivari-SP; in addition, just a few environmental education initiatives were developed with regards to this subject within the scope of municipal school education. In this sense, this work aims to analyze the biodiversity and wildlife conceptions from elementary school students in a rural school in the city of Capivari and employees of the region's mills and factories. It also aims to understand the strategies that teachers on this same school use to touch on the matter of conservation of biodiversity and regional wildlife with the students, in order to develop a process of participatory construction of an educational space in a perspective of critical environmental education, aiming at conservation of the jaguar (Puma concolor). In addition, a secondary study of wildlife in the rural area of the city was carried out using tools such as drawings and questionnaires completed by the participants of the research and also by searching for directly and indirectly traces for one month. The research was conducted in a qualitative approach and used as instruments of data collection questionnaires and focus groups with the students, interviews with the teachers and visitors of the educator space, and questionnaires with the workers of the São José mill. As a result of the students conceptions study, we observed that the students of the 5th and 4th year do not know how to explain what biodiversity and wildlife are, but they do know how to draw animals from the wild fauna that they have seen in the region, the teachers of the 4th and 5th year of the municipal school only use the content of the books adopted by the city government and the projects given by the Municipal Education Department, but it did not carry out environmental education projects in 2016 that aimed at the conservation of wildlife in the city. The educational space has a great participation from the school community, residents of the neighborhood and students from other schools. It is clear that the population encourages and supports the creation of spaces like this. Employees of the mill, when encountering a specimen of brown jaguar, would call the responsible bodies and not injure the animal. As a result of the preliminary study of the wildlife the following animals were found: otter, Tayra, maned wolf, anteater, small-tailed cat, jaguarondi, coati, bush dog, skunk and capybara.